2014
DOI: 10.1039/c4cp00598h
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency enhancement of black dye-sensitized solar cells by newly synthesized D–π–A coadsorbents: a theoretical study

Abstract: In this work, using the DFT and TDDFT, we have theoretically studied the electronic and optical properties of the two recently synthesized coadsorbents Y1 and Y2, which were aimed to enhance the efficiency of the black dye-sensitized solar cells. To determine the solvatochromic shifts, both the implicit and mixed implicit-explicit models have been used. The connection between the solvatochromic shifts and the changes of dipole moments in the excitation process is discussed. The difference in excitation charge … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
2
5
0
Order By: Relevance
“…À ions far away from the semiconductor surface and to efficiently act as an anti-aggregation agent. 60 Despite the lower efficiencies, the trends of the measured parameters are consistent with those in the original paper. 19 The stability of the investigated devices was assessed with J-V measurements at 1/3 Sun (Table 1; Fig.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…À ions far away from the semiconductor surface and to efficiently act as an anti-aggregation agent. 60 Despite the lower efficiencies, the trends of the measured parameters are consistent with those in the original paper. 19 The stability of the investigated devices was assessed with J-V measurements at 1/3 Sun (Table 1; Fig.…”
Section: Resultssupporting
confidence: 83%
“…19 A key role in this regard is played by the butoxyl chains on the donor part of the molecule, that are able to keep the oxidized I 3 ions far from the semiconductor surface, and to efficiently act as an antiaggregation agent. 60 Despite the lower efficiencies the trend of the measured parameters are however consistent with the original paper. 19 Stability of the investigated devices was assessed with J-V measurements at ⅓ Sun.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…These blue shifts may also be explained by using the fact that the dipole moments in the excited states are smaller than their corresponding ground state vectors. 53 Recent studies on excitation energies have shown that for charge-transfer (CT) excitations, the TDDFT calculations may lead to errors of the order of some eV, [54][55][56] and the use of range-separated XC functionals has therefore been prescribed. 57 The diagnostic parameter Λ, which quantifies the charge-transfer character of excitations 53,57 and takes the values 0 ≤ Λ ≤ 1, are calculated for the dominant transitions of RD dyes and the results are listed in Table 3.…”
Section: Absorption Spectramentioning
confidence: 99%
“…The description of detailed mechanisms involved at interfaces is not possible unless one uses computational methods. The density functional theory (DFT) 13,14 and its time-dependent extension (TDDFT) 15 have played significant roles in the design and engineering of electrochemical systems among which hydrogen evolution systems 16,17 and DSSC's [18][19][20][21][22] are the most common examples.…”
Section: Introductionmentioning
confidence: 99%